Effect of pharmacokinetically-relevant ivermectin concentrations on survivorship and fecundity of Anopheles coluzzii and Aedes aegypti in Burkina Faso: A laboratory experimental study - Emmanuel Sougué; Cheick Oumar W. Ouédraogo; Fabrice A. Somé; Greg Pugh; André B. Sagna; S. Rodrigue Dah; Saoudatou Bagayogo; Risnahar T. Ouédraogo; Mady Ndiaye; Sunil Parikh; El Hadji M. Niang; Brian D. Foy; et al. (PLoS ONE, 2026)
Background The control of vector-borne diseases is increasingly challenged by insecticide resistance widespread. Therefore, innovative vector control tools with alternative modes of action are urgently needed to support existing ones. Ivermectin (IVM), a broad-spectrum endectocide has been shown to exert lethal effects on mosquitoes, including Anopheles and Aedes species following blood meals taken from treated humans or livestock. In this study, we assessed the effect of IVM at concentrations equivalent to human plasma levels following mass drug administration (MDA), on the survival and fecundity of An. coluzzii and Ae. aegypti in Burkina Faso. The present study provides new insights into how IVM may impact differentially both malaria and arbovirus vectors, contributing to develop integrated strategies of vectors control. Methods Two laboratory experiments were conducted using 3–5-days old wild-derived female An. coluzzii and Ae. aegypti . Each experiment included four replicates per IVM concentration and was performed on separate dates. Mosquitoes were membrane fed with rabbit blood treated with five IVM concentrations (C = 112 ng/mL, C2 = 29 ng/mL, C3 = 15 ng/mL, C4 = 6.5 ng/mL, C5 = 2.5ng/mL), corresponding to the mean human plasma levels at 2, 4, 7, 14, and 28 days post-MDA with IVM at a dose of 3x300 µg/kg. A negative control with free-IVM (0.0 ng/mL) was also included. Mosquito mortalities were recorded daily for 7 days. Fecundity was measured by counting both laid and developed eggs (via ovary dissection). Results IVM significantly reduced the survival of An. coluzzii compared to the control group ( p < 0.001 ), with the risk of death increasing from 4.2-fold at the lowest concentration (2.5 ng/mL) to 64.2-fold at the highest (112 ng/mL). In contrast, IVM had no significant effect on Ae. aegypti ( p > 0.05 ), and the survival rate of control group did not differ from that of treatment groups. Additionally, for An. coluzzii , IVM significantly reduced both egg laying and egg development (p < 0.0001 and p < 0.001, respectively), whereas no significant impact on fecundity was observed in Ae. aegypti (all p > 0.80) . Conclusion IVM concentrations typically achieved in human plasma during MDA campaigns were sufficient to significantly reduce both survival and fecundity of wild type An. coluzzii , but had no measurable effect on Ae. aegypti . These findings highlight the species-specific response to IVM and support its potential role in integrated vector control strategies targeting malaria vectors in Africa.